-3-3(6v+1)=-7v+38

Simple and best practice solution for -3-3(6v+1)=-7v+38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-3(6v+1)=-7v+38 equation:



-3-3(6v+1)=-7v+38
We move all terms to the left:
-3-3(6v+1)-(-7v+38)=0
We multiply parentheses
-18v-(-7v+38)-3-3=0
We get rid of parentheses
-18v+7v-38-3-3=0
We add all the numbers together, and all the variables
-11v-44=0
We move all terms containing v to the left, all other terms to the right
-11v=44
v=44/-11
v=-4

See similar equations:

| 45-y-5*y-5=124 | | -3(2x-6)=4x+8 | | 3x³-27x=0 | | 5y-11-3y+6=0 | | X.3(2x-5)=2(3x-2 | | 3(x+9=7x-6 | | x+2÷9=3 | | 2x-5+x+9+4x-4x-10=180 | | 6(x-1)-5=2x+4(-4+x) | | x/​19.3=7.5 | | 8x-3x=8x | | (x-​3200)/​19.3=7.5 | | 6y+2=180 | | 5(v-8)=-10 | | |2x=7|3 | | -6x+18=-8x+23 | | X+(x*18/100)=3546910 | | h=4H | | 3x-15+6x-2=45 | | 5(4+n)=6n | | -3v+2=11 | | 24n=672 | | 4x-4x=10+5 | | -3x(3x-8)=3x | | 2(4x+3)=4(x−2)−2x | | 3(5-4m)-6m=123 | | 6+6n=5n+3 | | v-9=3v+5 | | 4n+1-7=18 | | 4(4a-2)-6a=-88 | | 2^x.3^x-1=72 | | 1000(9x-10)=50(846+100x) |

Equations solver categories